Acid Leaching Of Amang For Eventual Recovery Of Titanium Under Diffusion Limited System - Mansor, Mohamad Amir Syafiq (Universiti Sains Malaysia, 2017)
Leaching process of ‘Amang’ was carried out by using hydrochloric acid and sulfuric acid as leaching agent without any presence of catalyst. Leaching were tested at the worst condition where no agitation included in the whole process and kinetics was studied under diffusion limited system. Amang was characterized using a few techniques including PSD, XRF, XRD, LOI and SEM. XRF analysis shows that some elements presents in amang give a high percentage by weight including TiO2 (34%), Al2O3 (15%), SiO2 (18%), Fe2O3 (15%) and ZrO2 (8%). From XRD, major peak shown indicates the existence of major mineral bearing the titanium metal that is rutile and ilmenite. SEM of polished section proves that titanium bearing mineral was already liberated from other elements excepts for iron so it can be leached directly. The leaching was conducted by manipulating different parameters such as acid concentration, solid to liquid ratio and temperature. The novelty of the experiment is to test one factor at a time. At room temperature, two parameters were tested by using different concentration of sulfuric acid and different volume of acid to leach 10g of amang. 4M of acid concentration give higher weight loss of 1.25% after 4 hours of leaching. Meanwhile, ratio of 1:7 gives the highest weight loss of 0.56% when leached using 2M of sulfuric acid for 4 hours. Varying the temperatures, 80 oC of 2M sulfuric acid give highest weight loss of 3.18% after 4 hours of leaching. Testing the residue of amang after sample using XRF give the same amount of element in weight percent as raw sample. XRD analysis of leached residue shows that ilmenite has been leached because only TiO2 can be detected in two different phases of rutile and brookite.